2012
DOI: 10.1371/journal.pone.0036419
|View full text |Cite
|
Sign up to set email alerts
|

Influence of HLA-DRB1 and HLA-DQB1 Alleles on IgG Antibody Response to the P. vivax MSP-1, MSP-3α and MSP-9 in Individuals from Brazilian Endemic Area

Abstract: BackgroundThe antibody response generated during malaria infections is of particular interest, since the production of specific IgG antibodies is required for acquisition of clinical immunity. However, variations in antibody responses could result from genetic polymorphism of the HLA class II genes. Given the increasing focus on the development of subunit vaccines, studies of the influence of class II alleles on the immune response in ethnically diverse populations is important, prior to the implementation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 56 publications
2
71
0
Order By: Relevance
“…The full texts of these 162 studies were examined to determine whether they complied with eligibility criteria: 114 did not meet the inclusion criteria (see Additional file 3), 7 fulfilled the inclusion and quality criteria (Figure 1), and 41 studies potentially met inclusion and quality criteria. The authors of the 41 studies that potentially met inclusion and quality criteria were contacted, yielding a further 11 studies that met inclusion and quality criteria, providing a total of 18 studies that were included in the review [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] (Figure 1). Details of these 18 studies are shown in Table 1.…”
Section: Identification and Description Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The full texts of these 162 studies were examined to determine whether they complied with eligibility criteria: 114 did not meet the inclusion criteria (see Additional file 3), 7 fulfilled the inclusion and quality criteria (Figure 1), and 41 studies potentially met inclusion and quality criteria. The authors of the 41 studies that potentially met inclusion and quality criteria were contacted, yielding a further 11 studies that met inclusion and quality criteria, providing a total of 18 studies that were included in the review [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] (Figure 1). Details of these 18 studies are shown in Table 1.…”
Section: Identification and Description Of Included Studiesmentioning
confidence: 99%
“…The studies described by Lima-Junior in 2008 and 2012 [24,26] were conducted in the same area, but the participants were different.…”
Section: Pvdbp Region II Cross-sectional Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The HLA class II controls the immune response to p126-derived amino terminal peptide from P. falciparum [9]. The presence of HLA-DRB1 is associated with severe malaria [10][11][12] and is related to the high frequency of the IgG antibody response to the P. vivax circumsporozoite protein (CSP) and merozoite surface protein (MSP) [13][14][15]. The HLA-DQA alleles are associated with patients co-infected with circumsporozoite variants of P. falciparum in western Thailand [16], and the HLA-DQ1*0502 allele is associated with malaria in the Muong population in Vietnam [17].…”
Section: The Genomic Factors Associated With Vitamin D In Malariamentioning
confidence: 99%